2019
DOI: 10.1002/1873-3468.13622
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the putative rate‐limiting role of electron transfer in fatty acid desaturation using transfected HEK293T cells

Abstract: Elevated fatty acid (FA) levels contribute to severe metabolic diseases. Unbalanced oversupply of saturated FAs is particularly damaging, which renders stearoyl‐CoA desaturase (SCD1) activity an important factor of resistance. A SCD1‐related oxidoreductase protects cells against palmitate toxicity, so we aimed to test whether desaturase activity is limited by SCD1 itself or by the associated electron supply. Unsaturated/saturated FA ratio was markedly elevated by SCD1 overexpression while it remained unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Although double bonds can be formed at various positions up to 9, the first one must be created by a stearoyl-CoA desaturase between the carbons 9 and 10, which makes SCD activity rate determining for the overall desaturation process. It has also been demonstrated that SCD activity is not limited by the capacity of the associated electron transfer chain, so it is determined by the level of SCD enzyme itself [ 25 ]. Among the two human SCDs, SCD1 is highly expressed in most tissues including liver, adipose tissue, heart, lung, and the central nervous system, and its metabolic role is clear, the recently discovered SCD5 is present mostly in the central nervous system and some endocrine and reproductive organs, and its function is obscure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although double bonds can be formed at various positions up to 9, the first one must be created by a stearoyl-CoA desaturase between the carbons 9 and 10, which makes SCD activity rate determining for the overall desaturation process. It has also been demonstrated that SCD activity is not limited by the capacity of the associated electron transfer chain, so it is determined by the level of SCD enzyme itself [ 25 ]. Among the two human SCDs, SCD1 is highly expressed in most tissues including liver, adipose tissue, heart, lung, and the central nervous system, and its metabolic role is clear, the recently discovered SCD5 is present mostly in the central nervous system and some endocrine and reproductive organs, and its function is obscure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%